إستخدامات شبكات التواصل الإجتماعي فايسبوك وعلاقتها بالتغير الإجتماعي لدى الطلبة الجامعيين - ذيب, محمد (Universty of Eloued جامعة الشهيد حمة لخضرالوادي, 2021)
الملخص: أجريت الدراسة الموسومة بـ: إستخدامات شبكات التواصل الإجتماعي فايسبوك وعلاقتها بالتغير الإجتماعي لدى الطلبة الجامعيين. -دراسة ميدانية على عينة من طلبة جامعة الوادي – وبالتحديد على عينة من طلبة قسم العلوم الإجتماعية، في الفترة الممتدة من شهر نوفمبر 2017 إلى شهر ديسمبر 2020، بجامعة الوادي، على عينة قوامها 237 مفردة من طلبة قسم العلوم الاجتماعية بجامعة الوادي، وتمحورت إشكالية الدراسة حول: هل توجد علاقة بين إستخدامات شبكات التواصل الإجتماعي“فيسبوك“ والتغير الاجتماعي لدى الطلبة الجامعيين بقسم العلوم الإجتماعية؟، وللإجابة على هذا التساؤل تم تقسيمه للأسئلة التالية: هل توجد علاقة بين إستخدامات شبكات التواصل الإجتماعي ”فيسبوك“ وتغير القيم الأخلاقية لدى الطلبة الجامعيين بقسم العلوم الإجتماعية؟. هل توجد علاقة بين إستخدامات شبكات التواصل الإجتماعي وتغير السلوكيات لدى الطلبة الجامعيين بقسم العلوم الاجتماعية؟ هل توجد علاقة لإستخدامات شبكات التواصل الإجتماعي والأمن الفكري لدى الطلبة الجامعيين بقسم العلوم الاجتماعية؟. هل توجد هناك فروق ذات دلالة إحصائية في درجة متغيرات الدراسة تبعا لمتغير النوع (ذكور– إناث) لدى الطلبة الجامعين بقسم العلوم الاجتماعية؟ وهدفت الدراسة لوصف الظاهرة وكشف العلاقة بين إستخدامات شبكات التواصل الإجتماعي" الفيسبوك" والتغير الإجتماعي لدى الطلبة الجامعيين، وإستخدم الباحث المنهج الوصفي في الدراسة من أجل الإلمام بجوانب الموضوع، كما إستخدم الاستبيان كأداة لجمع البيانات في الدراسة الميدانية، وإستخدم برنامج الحزمة الإحصائية الاجتماعية spss في إصداره 23.0 لتحليل هذه البيانات والمعطيات، وخلصت الدراسة للنتائج التالية: وجود علاقة بين إستخدامات الفيسبوك والقيّم الأخلاقية لدى الطلبة الجامعيين، ولكن بدرجة متوسطة، وذلك بمتوسط حسابي (3.36)، حسب إستجابات أفراد العينة، وحسب وجهة نظرهم، وقدرت نسبة ذلك بـ (%82.30). وجود علاقة بين إستخدامات الفيسبوك وتغير السلوكيات لدى الطلبة الجامعيين، ولكن بدرجة متوسطة، قدّر متوسطها الحسابي بـ (2.82)، حسب إستجابات أفراد العينة وحسب وجهة نظرهم، وقدرت نسبة ذلك بـ (%68.80). وجود علاقة بين إستخدامات الفيسبوك والأمن الفكري لدى الطلبة الجامعيين، ولكن بدرجة متوسطة، وذلك بمتوسط حسابي (3.60)، حسب إستجابات المبحوثين، وحسب وجهة نظرهم، وقدرت نسبة ذلك بـ (%51.1) وجود علاقة إرتباط بين متغيرات الدراسة حسب إستجابات أفراد عينة البحث، فهذه المتغيرات مترابطة ببعضها البعض ومتداخلة، وأي خلل في أحد المتغيرات يؤثر في الآخر، وتبقى تلك العلاقة بدرجة متوسطة. وجود علاقة بين إستخدامات شبكات التواصل الإجتماعي والتغيّر الإجتماعي لدى الطلبة الجامعيين بقسم العلوم الاجتماعية، ولكن تبقى بدرجة متوسطة، وبمتوسط حسابي إجمالي قدّر بـ (3.26)، حسب إستجابات أفراد عينة البحث محل الدراسة. Abstract: The study entitled: The uses of social network "Facebook" and its relationship to social change among university students- A field study on a sample of Eloued University students. It was conducted specifically on a sample of students of the Social Sciences Department, from November 2017 to December 2020, at El Oued University, On a sample of 237 individuals from the Social Sciences Department, at El Oued University. And the problem of the study revolved about: Is there a relationship between the uses of social networks "Facebook" and social change among university students of the Social Sciences Department?, to answer this question, it is divided into the following questions: Is there a relationship between the uses of social networks "Facebook" and moral values change among university students of the Social Sciences Department? Is there a relationship between the uses of social networks "Facebook" and behavior change among university students of the Social Sciences Department? Is there a relationship between the uses of social networks "Facebook" and intellectual security among university students of the Social Sciences Department? Are there statistically significant differences in the degree of study variables according to the gender variable (male - female) among university students of the Social Sciences Department? The study aimed to describe the phenomenon and reveal the relationship between the uses of social networks "Facebook" and social change among university students, in order to be familiar with the aspects of the topic, the researcher used the descriptive approach in the study, and also used the questionnaire as a tool to collect data in the field study. The social statistical packages spss program, in its version 23.0, was used to analyze these data and data, and the study concluded with the following results: The existence of a relationship between the use of Facebook and the moral values among university students, but with a moderate degree, according to the responses of the sample members and according to their point of view, with a percentage estimated at (82.30%). The existence of a relationship between the use of Facebook and the behavior change among university students, but with a moderate degree, according to the responses of the sample members and according to their point of view, with a percentage estimated at (68.80%). The existence of a relationship between the use of Facebook and the intellectual security among university students, but with a moderate degree, according to the responses of the sample members and according to their point of view, with a percentage estimated at (51.1%). The existence of a correlation between the study variables according to the responses of the sample members. These variables are interrelated with each other, and any defect in one affects the other. This remains that relationship to a moderate degree. The existence of a relationship between the use of social networks and the social change among university students of the Social Sciences Department, but remains to a moderate degree, according to the responses of the sample members.
دراسة ميدانية على عينة من طلبة جامعة الوادي –
أطروحة دكتوراه تخصص:أطروحة دكتوراه في علم الاجتماع تخصص علم الاجتماع
Keywords: شبكات التواصل الاجتماعي؛ فيسبوك؛ التغيرالاجتماعي؛ الطالب الجامعي؛ الجامعة.; Social networks; Facebook; Social change ; university student; University